Konsentrasi Serum Anjing yang Optimum untuk Menumbuhkan dan Memelihara Babesia canis dalam Biakan - Astyawati, Tutuk; Wulansari, Retno; -, Cahyono; Ardhiansyah, Ferry; Rumekso, Ari; -, Dhetty (Jurnal Veteriner; Vol 11 No 4 (2010))
The use of cultivation system in vitro is very important in the future study of Babesia canis. Theaim of this study was to cultivate B. canis in vitro using RPMI media with different concentration of dogsera. B. canis infected erythrocytes were collected from splenectomized infected dog. Parasites werecultivated with RPMI 1640 medium supplemented with normal dog sera at the concentration of 10%, 20%and 40%, the culture were then incubated in 5% CO2 , 37oC temperature for 17 days and subcultured every48 hours. The Percentage of Parasitized Erythrocytes (PPE) in culture with 10% dog serum was significantlylower than those 20%, and 40% The used of 20% and 40 % sera were better than 10%. It is recommendedthat 40 % serum can be used for initiation phase of cultivation, whereas 20% concentration were used formaintenance of the culture.
Keywords: Babesia canis, Cultivation, Percentage of Parasitized Erythrocytes